Plasmonic Heating-Promoted Photothermal Synthesis of α-Cyanoacrylonitriles Over Au/h-BN Catalysts - Liang, Ce; Zhang, Yuanyuan; Zhang, Bin; Liu, Xin-Miao; Gao, Guo-Lin; Cao, Jingyan; Xu, Ping (Frontiers in Chemistry, 2021)
Plasmonic nanoparticle-involved materials play an essential role in the field of photothermal conversion. Herein, we report the application of photothermal heterogeneous catalysts consisting of gold nanoparticles decorated on defect-rich h-BN sheets (Au/h-BN) for the photocatalytic synthesis of α-cyanoacrylonitriles under mild conditions. It has been demonstrated the –NH2 groups present in the defect-rich h-BN act as the catalytically active sites, while plasmonic heating from the gold nanoparticles can drive the reaction by providing local heat. Au/h-BN catalyst can work for a broad substrate scope in the synthesis of α-cyanoacrylonitriles, and a plausible –NH2 group-involved reaction mechanism has been proposed. This work may open up new avenues in photothermal catalysis by combining plasmonic materials and catalytic sites in one system.